Entrepreneurship the art, science, and process for success - Bamford, Charles E.; Bruton, Garry D. (McGraw Hill LLC, 2022)
"This book presents a systematic and thorough means for students and potential entrepreneurs to think through their venture and the rich range of concerns around it three core tenets to starting an entrepreneurial venture: 1. Science of practice as the heart of starting and running a successful entrepreneurial venture. 2. Art of turning an entrepreneurial venture into a success. 3. Processes that tie these two areas together into a coherent and organized business."--Provided by publisher.